(untitled) (Archaeologia Adriatica, 2017)
In grave 134 in the late Roman cemetery of Štrbinci (Đakovo, NE Croatia), dated from the mid 4th to the early 5th century, which held a child of 2-3 years of age, the following grave goods were recovered: 1– a copper alloy bulla; 2 – a copper alloy lunate pendant; 3 – a silver lunate pendant; 4 – a poorly preserved headdress (diadem) composed of three small rectangular plates made of yellowish glass, most probably originally fixed onto a gilded copper alloy band; 5 – 65 beads made of whitish, blue, and green glass; 6 – a copper alloy bracelet; 7 – a pottery jug. The grave was published within the paper on the 2007-2008 campaign of excavations at Štrbinci, but without a detailed discussion of individual grave finds. In this contribution these finds are discussed from the point of view of their apotropaic function and gender role as grave goods. The conclusion reached is that the child was most probably a girl, who had been buried with much care and a pronounced wish to get every protection possible in the otherworld.